2021
DOI: 10.3390/nu13072239
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sport Nutrition Knowledge on Body Composition and Perceptions of Dietary Requirements in Collegiate Athletes

Abstract: Sport nutrition knowledge has been shown to influence dietary habits of athletes. The purpose of the current study was to examine relationships between sport nutrition knowledge and body composition and examine potential predictors of body weight goals in collegiate athletes. Participants included National Collegiate Athletic Association Division III women (n = 42, height: 169.9 ± 6.9 cm; body mass: 67.1 ± 8.6 kg; fat-free mass: 51.3 ± 6.6 kg; body fat per cent: 24.2 ± 5.3%) and men (n = 25, height: 180.8 ± 7.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 36 publications
4
41
0
2
Order By: Relevance
“…In a direct comparison to the only other study that utilized this assessment tool, the developers of the survey found a mean score of 15.9 and a correct score percentage of 55.4% in their population of adult athletes, a majority of whom (61.9%) were collegiate athletes and female (70.8%) [ 26 ]. Regardless, based on the previously reported cutoff of 75% for exhibiting “adequate” or “excellent” knowledge [ 22 , 25 , 29 ], our results are in line with the majority of studies showing inadequate nutrition knowledge in collegiate athletes [ 16 ]. Furthermore, these results indicate that NCAA DIII collegiate athletes, who typically lack robust institutional resources, are particularly in need of sport nutrition education and could benefit from greater institutional support.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In a direct comparison to the only other study that utilized this assessment tool, the developers of the survey found a mean score of 15.9 and a correct score percentage of 55.4% in their population of adult athletes, a majority of whom (61.9%) were collegiate athletes and female (70.8%) [ 26 ]. Regardless, based on the previously reported cutoff of 75% for exhibiting “adequate” or “excellent” knowledge [ 22 , 25 , 29 ], our results are in line with the majority of studies showing inadequate nutrition knowledge in collegiate athletes [ 16 ]. Furthermore, these results indicate that NCAA DIII collegiate athletes, who typically lack robust institutional resources, are particularly in need of sport nutrition education and could benefit from greater institutional support.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the relevant literature has consistently shown that the dietary intakes of collegiate athletes do not typically meet the recommended nutrient intakes [ 6 , 7 , 36 , 37 , 38 ]. This could potentially be due to a mismatch between perceptions of dietary requirements and actual needs [ 25 ]. Thus, while dietary habits may be prudent, gross intakes may not be sufficient, placing athletes at risk for LEA and developing RED-S [ 10 ] and overtraining syndrome [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite nutritional education initiatives [ 12 ] and access to healthcare professionals, active-duty soldiers, regardless of rank, indicate that they feel that their nutrition is “out of their control”, stating that the current environmental and cultural norms of military life discourage healthful choices while encouraging poor ones [ 13 ]. Similarly, among college athletes, a lack of time (31.8%), a lack of knowledge (28.6%), and financial restrictions (21.0%) are the most frequently reported obstacles to optimal nutrition [ 14 ].…”
Section: Introductionmentioning
confidence: 99%